Necesidad de reformar el art. 81 de la Ley Orgánica del servicio público por cuanto discrimina los derechos constitucionales de los adultos mayores - Granja Cajas, Ana Lucia (2014)
The history is filled with a constant change resulting from life itself. Considering all the aspects that make this life, we find as an important part of it the work people do, which like everything else, has been transformed. His transformation has taken place not in the execution itself, because we still find activities that are done in a manual way, but there are also other activities where technology performs almost everything. What does have changed is the way people relate to each other, depending on the job. According to this we found that performing a work as an employee, is regulated by labor laws that protect both the employer and the worker seeking thus avoid the various kinds of exploitation to which the worker was exposed. Among the achievements that workers have achieved, we can quote the recognition of work as worthy to live and not as something that was done because of a punished by those who could not be seen like people, so based on international efforts at the time nearly every country in the world, respects specific workers-rights that are already considered as more than mere dead letter, and this is how these constitutional rights form are in almost the entire world. In Ecuador, the Constitution establishes work as a duty and a right, a way to earn a decent living. The same Constitution promulgates that is the duty of the state to promote the opportunities to create jobs, to ensure access to it to all Ecuadorians. It also establishes that in the Ecuadorian state all people will be treated equally, without being subject to discrimination and established. In Art.11, that "The exercise of the rights will be governed by the following principles: Two. All people are equal and enjoy the same rights, duties and opportunities. No one shall be discriminated against on grounds of ethnicity, place of birth, age , sex , gender identity , cultural identity ... ", So if that is the constitutional premise, which manifests the Public Service Law. “Article 81, paragraph 6 " the public employees at seventy years of age - who meet the requirements of the laws of social security for retirement- necessarily have to retire from the public service "; becomes clear is unconstitutional because it clearly going against people who has reached seventy years of age, regardless of any situation, just because of the fact that he turned seventy. It is true that some countries share the point of view to establish and age limit for the people to retire, it is also true that not all the countries have established a certain age. Retirement in these countries is not an obligation is a right. It can be seen then that on one hand our Constitution, framed all the principles of respect for a specific society, but otherwise is the same state uses its authority to establish a law which transgresses the whole Constitution. Employment, according to our Constitution, is an obligation. Our way of living depends on the way we do our job. We intend to say that our job is the access to the various goods that are essential for us to have a healthy, peaceful existence and our life quality. Therefore stop working at seventy years means stop having a good quality of life, lose the dignity and decorum or, mostly, is no longer a subject of rights, and they don´t have the constitutional protection that everybody else still does.